Improvement of the turn-down ratio of gas turbines by autothermal on board syngas generation. (30th June 2017) - Baumgärtner, Max H.; Sattelmayer, Thomas
Abstract: The low reactivity of natural gas leads to a sudden increase of carbon monoxide (CO) and unburned hydrocarbons (UHC) emissions below a certain load level, which limits the part load operation range of current utility gas turbines in combined cycle power plants (CCPP). The feasibility of catalytic autothermal syngas generation directly upstream of gas turbine burners to improve burn-out at low flame temperatures is studied in this paper. The adiabatic reformer is supplied with a mixture of natural gas, air and water and generates syngas with high reactivity, which results in better low-temperature combustion performance. Substitution of part of the natural gas by syngas provides the opportunity of lowering overall equivalence ratio in the combustion chamber and of extending the operation range towards lower minimum power output without violating emission limits. A generic gas turbine with a syngas generator is modelled by analytic equations to identify the possible operating window of a fuel processor constrained by pressure loss, low and high temperature limits and carbon formation. A kinetic study shows good conversion of methane to syngas with a high hydrogen share. A calculation of the one-dimensional laminar burning velocity of mixtures of syngas and methane and the assessment of the corresponding Damköhler number show the potential for lowering the minimum equivalence ratio with full burn-out by fuel processing. The study shows that such a fuel processor has a possible operating range despite the before mentioned constraints and it has potential to reduce the lowest possible load of gas turbines in terms of thermal power by 20%.